Analisis Pengaruh Penggunaan Aplikasi Digital dan Keputusan Pembelian terhadap Pendapatan Pelaku Usaha di Kota Bukittinggi : Studi Kasus: Pedagang kaki Lima di Lapangan Wirabraja Kota Bukittinggi - Nadia Ali Putri; Andis Febrian (Lembaga Pengembangan Kinerja Dosen, 2025)
The goal of this research is to find out how much money the street sellers at Wirabraja Field make from people's choices to utilise digital apps while making purchases. This research surveyed thirty street sellers from Wirabraja Field in Bukittingii City. The researchers in this study used a method called complete sampling to choose their samples from the whole population. This study's data analysis method relied on multiple regression analysis, executed using the SPSS 25 statistical programme. Research and hypothesis testing have shown that business actors at street vendors in Wirabraja Square, Bukittinggi City, see a favourable and statistically significant increase in their revenue when they utilise digital apps. In Wirabraja Square, Bukittinggi City, the revenue of street sellers is positively and significantly impacted by consumer purchasing choices. The revenue of business players in Wirabraja Square, Bukittinggi City, is positively and significantly impacted by the usage of digital apps and purchase choices. Business actor income (Y) is reliant on two independent variables, use of digital applications (X1) and purchasing decisions (X2), which together account for 0.416, or 41.6% of the total. Entrepreneurial literacy, financial literacy, and other factors not included in this research account for the remaining 0.584, or 58.4%.